Improving Wudu Techniques Through a Media-Assisted Demonstration Method Using IFP in Islamic Education Classes in Kindergarten Class B - Sinta Wulandari (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study aims to improve children's ability to understand and practice the correct wudhu procedure through the application of the demonstration method assisted by Interactive Flat Panel (IFP) media in Islamic Religious Education (PAI) learning in TK B group at KB As-Salam. This study used a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 15 children in TK B KB As-Salam. Data were collected through observation, performance assessment, and documentation. The results showed that the implementation of the demonstration method assisted by IFP media significantly improved children's ability to understand the sequence and procedure of wudhu. In the pre-cycle, only 33.3% of children achieved the Developing as Expected (BSH) criterion. After the first cycle, it increased to 60%, and in the second cycle it reached 86.7%. Thus, the use of IFP media displaying videos, sequential images, and interactive animations of wudhu procedures is able to strengthen young children's visual understanding and improve the effectiveness of the demonstration method in PAI learning in kindergarten.